The Pengaruh Penyuluhan Kesehatan Penanganan Scabies (Sarcoptes Scabiei) Terhadap Tingkat Pengetahuan Swamedikasi Santri Pondok Pesantren Darussalam : Pengaruh Penyuluhan Kesehatan Penanganan Scabies (Sarcoptes Scabiei) Terhadap Tingkat Pengetahuan Swamedikasi Santri Pondok Pesantren Darussalam - NABILA RADIAHAYYA; FAUZIAH; SILMA KAAFFAH (Universitas Hang Tuah, 2026)
Scabies is a skin disease caused by the Sarcoptes scabiei mite, and is often suffered by individuals who live in groups such as dormitories, Islamic boarding schools, densely populated housing. Knowledge plays an important role in handling the transmission of scabies by practicing personal hygiene or by self-medication. This study aims to determine the level of knowledge of sel-medication in handling scabies in student at Islamic Boarding School in Purwokerto. The study was conduxted using a uestionnaire that had been tasted for validity and reliability through a one group pre-post design approach, which was conducted in march 2024 using a systematic random sampling technique and a sample of 55 students was obtained. Based on the results of the Cronbach alpha reliability test were reliable. The results of the univariate analysis showed that the majority of respondents were aged 15-20 years and female. The results of the bivariate anaysis of the Wilcoxon test showed that the level of khowledge of students before and after the intervention increased significantly (p-value < 0.05), namely from the good category of 61.8% to 89.1% and the sufficient category from 38.2% to 10.9%. in conclusion, periodic education is needed to provide information to student so that students’ knowledge increases further. Keywords : level of khowledge, scabies, pre-post, questionnaire, systematic random sampling